Quality of Life in Patients with Skin Diseases Attending a Public Healthcare Institute of Quetta City, Pakistan - Ghafoor, Rashid; Saleem, Fahad; Iqbal, Qaiser; Hassali, Mohamed Azmi; Hashmi, Furqan Khurshid; Haider, Sajjad; Anwar, Muhammad; Uddin, Zaheer; Salman, Muhammad (Journal of Pharmacy Practice and Community Medicine)
Background: The current study is aimed to document the Dermatology Life Quality Index (DLQI) of patients with skin disorders attending a public healthcare institute in Quetta city, Pakistan. Methods: A questionnaire based, cross-sectional study was planned for this research. The study was conducted at Bolan Medical Complex Hospital, Quetta. A response based, double design sampling method was used to identify the sample required for the study. Patients were asked to answer the Dermatology Life Quality Index (DLQI) for the assessment of QoL. SPSS v. 20 was used for data analysis. The Chi Square test was used for cross tabulation analysis and p < 0.05 was considered statistically significant. Results: Eight hundred and forty six patients responded to the survey. Mean DLQI score for the current cohort was 16.76 ± 2.54 indicating a very large effect of skin diseases on patient’s QoL. Symptoms and feelings reported mean score of 4.21 ± 0.9 out of 6 followed by daily activities and leisure (3.9 ± 1.1 and 3.8 ± 0.9 respectively). Educational level and income were significantly associated with various components of DLQI (P < 0.05). Conclusion: A large impact on QoL was observed among patients with skin disorders. Findings of the study suggest that serious efforts are needed to reduce the effect of educational and economic factors in order to improve the QoL of patients with skin disorders in Quetta city, Pakistan.
Keywords: Quality of life; Skin diseases; Public healthcare institute; Quetta city; Pakistan